Re-theorizing the collective action to address the climate change challenges: Towards resilient and inclusive agenda - Mehan, Asma (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2023)
Climate change poses a significant risk threatening the livelihood of people, communities, and cities worldwide. The stakes cannot be reduced to zero, so there is a constant need to re-theorize the collective action to address the climate change challenges. Doing so requires planning to reduce vulnerability to climate change. One of the most crucial challenges facing scientists, academics, citizens, and policymakers today is whether the collaborative, inclusive, and resilient climate change action can be implemented, assessed, and achieved. To respond to this question, this research aims to re-theorize, de-conceptualize, and analyze the collective effort to address the climate change challenges. First, the paper conceptualizes climate change resiliency as the ability to anticipate, prepare for, and respond effectively to climate-related risks, hazards, and threats. The existing challenges toward implementing resilient and inclusive climate change action have been analyzed. The paper theorizes the urban commons and collaborative governance to theorize collective efforts. This article concludes by identifying some critical determinants for the up‐scaling of collective action to address the climate change challenges. It can be supposed that any future inclusive and resilient collective action to address climate change is based on social learning to support decision-making, emphasizing inclusion and equity, which came in line with the United Nation’s 2030 SDGs.